KANDUNGAN LOGAM BERAT TIMBAL (Pb) DAN KADMIUM (Cd) PADA Anadara granosa DI PANTAI NONGSA KOTA BATAM UNTUK PENYUSUNAN LEMBAR TUGAS SISWA PADA KONSEP PENCEMARAN AIR DI SMA - Melisa Suryan Suryan; Nursal '; Elya Febrita Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Nongsa is Batam eastern coastal area which is crowded with a variety of industrial activities, transportation and domesti. The waste products of these activities will result in waste of heavy metals Pb and Cd which can pollute the surrounding waters. In order to investigate the quality of coastal waters in the nongsa beach, Batam city,  the measurement of heavy metals lead and cadmium in sea water, sediment and Anadara granosa has been done in June 2014 with a survey method. Results of measurement used for the preparation of the student assignment sheet on the concept of water pollution through the stages of analysis, design, and development. The average heavy metal Pb content in sea water is 2,760 ppm, in sediment is 3,870 ppm and in Anadara granosa is 1,460 ppm. While the average heavy metal content of Cd in seawater is 0,032 ppm, in sediments is 0,029 ppm and in Anadara granosa is 0,081 ppm. The results of research can be used as material for the preparation of the student assignment sheet on the concept of water pollution in high school with category Very Good. Meanwhile, to ensure the quality of this product, the testing steps still need to be followed up to the stage of Implementation dan Evaluation. Keywords: heavy metals lead (Pb) and cadmium (Cd), water pollution, Anadara granosa, student assignment sheet